Prospective analysis of penile length changes after radical prostatectomy. (2nd December 2013) - Berookhim, Boback M.; Nelson, Christian J.; Kunzel, Brian; Mulhall, John P.; Narus, Joseph B.
Abstract : Objectives: To assess the impact of radical prostatectomy (RP) on penile dimensions. To assess the impact of phosphodiesterase‐5 inhibitor (PDE5i) use on penile length changes. Patients and Methods: Men undergoing RP were enrolled in this prospective study before surgery. Demographic, clinical and PDE5i frequency‐of‐use data were collected. Erectile function was measured using the erectile function domain (EFD) of the International Index of Erectile Function. A single evaluator measured stretched flaccid penile length (SFPL) before RP, and at 2 and 6 months after RP. Repeated measures analysis was used to test differences in SFPL between timepoints. Pearson correlation was used for univariate analyses and multiple regression was used for multivariable analysis. Results: A total of 118 patients were evaluated at baseline, with 76 and 63 patients evaluated at 2 and 6 months, respectively. At 2 months, there was a 2.4‐mm mean decrease in SFPL, while at 6 months there was no significant difference. At 6 months, those subjects who took a daily PDE5i had no SFPL loss ( n = 36, 1±6.7 mm gain, P = 0.37 compared with baseline), while those subjects who did not consistently take a PDE5i had SFPL loss ( n = 27, 4.4±6.6 mm loss, P < 0.002 compared with baseline). In multivariable analysis, PDE5i use at 6 months and 6‐month EFD score without on‐demand PDE5i were significant predictors of 6‐month SFPL loss, suggesting that an increase in these variables leads to SFPL preservation. Conclusions: In this rigorously conducted prospective study of SFPL changes after RP, there was evidence of SFPL loss at 2 months, but not at 6 months after RP. PDE5i use moderated SFPL loss, with patients who regularly used PDE5i having no loss in SFPL.